Flowrate targeting algorithm for interplant resource conservation network. Part 1: Unassisted integration scheme - Chew, Irene M. L. (Animo Repository, 2010)
This paper is part 1 of a series describing a new algorithm for targeting minimum fresh resource and waste flow rates for an interplant resource conservation network (IPRCN). The IPRCN enables the reuse of the excess process sources among different networks, which reduces the consumption of fresh resource and generation of waste simultaneously. Four hypothetical examples are presented to illustrate both concentrationand property-based utility gas and water integration problems. In addition, the proposed targeting algorithm is adapted in the synthesis of total resource network, where the minimum regeneration and waste treatment flow rates can be targeted prior to the detailed design of an IPRCN. © 2010 American Chemical Society.